Preactivated thiomers: evaluation of gastroretentive minitablets - Hauptstein, Sabine (Int J Pharm, 2013)
The object of this study was to evaluate the potential of a recently developed preactivated thiolated pectin derivative as mucoadhesive excipient in drug delivery to the gastric cavity. Pectin (Pec) was chemically modified with L-cysteine (Cys). The free thiol groups of resulting thiomer were activated with 2-mercaptonicotinic acid (MNA) in order to improve stability and reactivity of attached thiol groups over a broad pH range. Multiunit dosage form properties of the resulting conjugate (Pec-Cys-MNA) were compared to unmodified pectin and the intermediate thiolated using rosuvastatin calcium as a model drug in loaded minitablets. Obtained results were compared with unmodified pectin and the intermediate thiolated pectin. Approximately half of attached thiol groups (507 μmol/g polymer) have been preactivated. Minitablets were evaluated regarding mucoadhesive properties, hardness, disintegration behavior, swelling characteristics and release of rosuvastatin calcium. Mediated by covalent bonds between the polymer and cysteine-rich subdomains in mucus, total work of adhesion increased more than 5-fold. The modification had no impact on hardness of compressed tablets but implementation of the aromatic ligand went along with reduction in hydrophilic properties. Disintegration time was prolonged more than 2-fold while water uptake capacity increased. Weight gain for Pec-Cys-MNA was at least 16-fold. Further, a sustained release of rosuvastatin calcium over 36 hours was determined. Neither biodegradability nor CaCo-2 cell viability was affected. The study shows that Pec-Cys-MNA is a promising excipient for the development of mucoadhesive gastric dosage form.